The constitutionalization of human rights law : implications for refugees - Meili, Stephen E., 1956- (Oxford : Oxford University Press, 2022)
'The Constitutionalization of Human Rights Law' analyses how lawyers representing refugees use human rights provisions in national constitutions to close the gap between the Law and its implementation. The book examines how laws are adapted to suit social, political, and legal contexts, focusing on Colombia, Mexico, South Africa, Uganda, and the US.
This edition also issued in print: 2022.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on November 1, 2022).
Keywords: Refugees -- Civil rights; Refugees -- Legal status, laws, etc; Human rights; Constitutional law; Law; International law